Evaluation of User Errors in Entering Vechile Categories at Bakauheni Port - Yulia Puspita Sari; Febriyanti Himmatul Ulya; Nopa Eliza (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2026)
Bakauheni Port is the main ferry port connecting the islands of Sumatra and Java via the Sunda Strait, with extremely high volumes of logistics activity. The port is managed by PT. ASDP Indonesia Ferry and plays a vital role in the movement of people and vehicles between the islands. The booking of ferry tickets via the Ferizy app is still considered suboptimal, and data entry errors frequently occur. This study aims to evaluate the accuracy of vehicle category input by service users. The results found that between January and April 2025, there were 1,011 vehicles for which the vehicle category was incorrectly entered. This has an impact on the process at the port’s entry gates, thereby slowing down service and causing long queues. One of the main causes is a lack of understanding among users regarding vehicle category classification.